2020
DOI: 10.1002/ecy.3231
|View full text |Cite
|
Sign up to set email alerts
|

Species pool size alters species–area relationships during experimental community assembly

Abstract: The species pool concept has advanced our understanding for how biodiversity is coupled at local and regional scales. However, it remains unclear how species pool size, the number of species available to disperse to a site, influences community assembly across spatial scales. We provide one of the first studies that assesses diversity across scales after experimentally assembling grassland communities from species pools of different sizes. We show that species pool size causes scale‐dependent effects on divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 47 publications
(76 reference statements)
2
32
0
Order By: Relevance
“…Previous studies regarding species-area relationships suggest that the increase in habitat area increases the available niche space, allowing more species to coexist and increasing diversity (De Camargo & Currie, 2015;Vellend et al, 2017). Biodiversity varies with spatial scales, representing that it may be limited by species interactions and/or randomness at the smaller spatial scales, whereas greatly controlled by dispersal and evolutionary history of the species pool at the broader spatial scales (Catano et al, 2021;Leibold & Chase, 2017).…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies regarding species-area relationships suggest that the increase in habitat area increases the available niche space, allowing more species to coexist and increasing diversity (De Camargo & Currie, 2015;Vellend et al, 2017). Biodiversity varies with spatial scales, representing that it may be limited by species interactions and/or randomness at the smaller spatial scales, whereas greatly controlled by dispersal and evolutionary history of the species pool at the broader spatial scales (Catano et al, 2021;Leibold & Chase, 2017).…”
Section: F I G U R Ementioning
confidence: 99%
“…Scaling-up the research of biodiversity and ecosystem functions relationship is necessary for extending the ecosystem functioning and stability from local communities to broader, heterogeneous regional communities related to restoration and conservation planning (Catano et al, 2021;Chase et al, 2018;Gonzalez et al, 2020). At the regional scale, this study provides insight into the significance of the sizes of the regional communities in modulating the relationships of multiple facets of biodiversity with woody productivity.…”
Section: Embracing Scale Dependence Of the Bpr At The Regional Communitiesmentioning
confidence: 99%
“…The other seven protected areas are within the coastal region encompassing a spatial extent of ~12,000 km 2 , with an average linear geographical distance of 159.5 ± 91 km between areas. We delimited a similar spatial extent for each region (Figure 1) to prevent the number of species within and across regions from being affected by species-area relationships (Catano et al, 2020). Furthermore, we selected local communities considering that their geographical isolation across regions should be similar to geographical isolation within each region.…”
Section: Species Occurrence Datamentioning
confidence: 99%
“…Specifically, high N availability decreased species diversity in the first few years after restoration, but increased diversity 15 years following restoration as long‐term fertilization increased the cover of forb species relative to dominant grass species (Baer et al., 2020). Recent work has also shown that the importance of the species pool size varies across spatial scales (Catano et al., 2021). In larger areas, enhanced environmental heterogeneity likely leads to greater species sorting, resulting in higher species richness.…”
Section: Restoration Experiments In Grasslands Demonstrate the Importance Of Interacting Filtersmentioning
confidence: 99%